Did the COVID-19 pandemic make the police work more difficult? - Kutnjak Ivković, Sanja (Policing during the COVID-19 pandemic, 2024)
This chapter explores the police officer views about whether their work has become more difficult during the pandemic. Based on the survey of patrol officers in six countries (Bosnia and Herzegovina, China, Croatia, the Philippines, Slovenia, the United States), we analyze their assessments of work difficulty and tease out the factors related to their assessments, both the factors that could make their work easier (e.g., fewer calls for service, fewer arrests for minor crimes) and the factors that could make their work more difficult (e.g., fear of being infected with COVID-19, use of personal protective equipment, police agency effectiveness in dealing with the pandemic, level of cooperation from the community). Our multivariate models reveal that the lack of enthusiasm for work, higher levels of stress, being married, and not evaluating positively the police agency’s efforts in dealing with the pandemic are all related to the perceptions that the job has become more difficult during the pandemic. We note strong country effects on the perceptions of job difficulty.